PENGARUH MUTASI PADA GEN LEPTIN TERHADAP TEBAL LEMAK PUNGGUNG DAN SKOR KONDISI TUBUH PADA SAPI PERANAKAN ONGOLE - Nena Hilmia; Dedi Rahmat; Muhammad Fatah Wiyatna; Dudi Dudi; Riki Akbar Rosidin; Didik Nurul Hadi (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2021)
Mutation on leptin gene affect leptin function as  one of the hormones  which contribute to body fat deposition.  This research aims to determine the effect of R25C and R25H mutations on the leptin gene toward  back fat thickness and Body Condition Score (BCS) in Ongole Grade cattle. The study was conducted with a quasi-experimental method, using completely randomized design. The treatments in this study were genotypes differences was, namely CC, TT and AA.  This research used  sixthteen heads of Ongole Grade Cattle  aged ± 2 years, and was reared for 60 days intensively. The feed  consisted of forage and concentrate with a ratio of 25: 75, as much as 3% dry matter of body weight and drinking water was given ad libitum. The backfat thickness was estimated using ultrasound performed on 4.5-6.5 MHz frequency, with depth of 8.8-13 cm, BCS was assessed visually by using 1 – 5 score.  The backfat thickness data were analyzed by variance component and BCS data was analyzed by Kruskal Wallis. The results showed average of backfat  thickness  CC, TT and AA genotype were  3.14 mm,  2.9 mm and 3.57 mm, respectively. The  body condition score for CC, TT and AA genotype were  3.54, 3.63 and 3.46  respectively.  The Mutation of leptin gene on  R25C and R25H have not effect to backfat thickness and body condition score in PO cattle.